Some Empirical Evidence of Loan Loss Provisions for Albanian Banks - Elona Dushku (Journal of Central Banking Theory and Practice, 2016)
In this paper we used a panel of Albanian banks for the period 2004-2014 to examine the main determinants of loan loss provisions. In addition, we tested how the latest crisis has affected provisioning behaviour of the banks. We find that loan loss provisions of banks are driven by non-discretionary components and economic fluctuations. Furthermore, we find a positive and significant result between earnings before interest, taxes and provisions and loan loss provisions, thus confirming the income smoothing hypothesis. Our estimated results do not support the capital management and signalling hypotheses. We also find that the global crisis has contributed significantly to the procyclicality of loan loss provisioning in Albania and banks continued to do income smoothing during the crisis.
Keywords: G21; C33; C36; 330; Loan loss provisions; Procyclicality; Income Smoothing; Albanian banks; Dynamic GMM.